From EU battlegroups to Rapid Deployment Capacity: learning the right lessons? - Meyer, Christoph O; Osch, Ton Van; Reykers, Yf (International Affairs, 2024)
The article uses the case of the development of the European Union Battlegroups to the Rapid Deployment Capacity (RDC) to better understand the changing learning capacity of the EU in its military Common Security and Defence Policy (CSDP). The article develops a theoretical framework to capture the most significant factors affecting learning by drawing on insights from the literatures on organizational learning and policy failure, with a specific focus on military organizations and CSDP. This framework is then used to study to what degree the EU has learnt the right lessons from the creeping failure of the Battlegroups, which factors affected learning, and to what degree the EU suffers from specific learning pathologies. The article draws on elite interviews, secondary and grey literature, and the high-level practitioner experience of one author. It finds that the EU has improved its learning capacities and correctly identified most of the military-operational root causes of the failure, yet struggled to correctly identify or address the political–strategic ones. This article offers insights to practitioners on where to best target efforts to improve learning. The theoretical framework could help to illuminate the challenges of political–military learning in multi-national regional organizations under difficult epistemic conditions.